Introducing and assessment of FAIR principles of education in teaching biochemistry to I year MBBS students - Jain, Suman; Mahajan, Neeraj; Sogani, Sonal; Bapna, Anju (International Journal of Research in Medical Sciences, 2020)
Background: Recent curriculum is theory based where students just mug up and reproduce in exam with less understanding. It is Exam and marks oriented education. Students show less interest in classes. Presently FAIR (Feedback, Active learning, Individual learning and Relevance) principles of application are practically missing, according to this model students will be naturally motivated to learn. Students will take more responsibility for their own learning. By applying these principles we will improve the effectiveness and efficiency of learning and enhancing learning among students. The objective was to design an effective educational strategy using certain principles of education such as FAIR. Methods: The first batch of the Integrated Curriculum students of the I MBBS program formed the study population. Certain principles of education such as Feedback, Active learning, Individualization of learning and relevance that have been advocated for use to enhance learning, were applied in educational strategies for the implementation of the Integrated Curriculum. Results: By Implementing the FAIR model of integrated curriculum the scores obtained during evaluation and the positive student response validated the enhancement of learning objectively and subjectively. Conclusions: Our collective experience convinced us that designing a curriculum with FAIR model was well worth. 95% students felt it is advantageous with negative perception 35% of students, they felt lengthy and time consuming.